Anxiety and Concentration of Tennis Athlete - Rices Jatra; Septian Raibowo (Universitas Bengkulu, 2021)
The purpose of this research to understand the correlation between anxiety and the concentration of tennis athletes. The subjects of this study were tennis athletes who entered the qualifying round in the